2009
DOI: 10.1111/j.1348-0421.2009.00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of cytolethal distending toxin‐producing Escherichia coli from children with diarrhea in Japan

Abstract: In the present study, we examined the prevalence and characteristics of CTEC among diarrheal children in Japan during a year-long surveillance study. A PCR-RFLP assay for the detection and differentiation of five types of E. coli cdtB gene (types I through V) was developed, and 362 stool specimens collected from patients reporting to pediatric departments in two hospitals were analyzed. Of the 35 samples (9.7%) that were positive for the cdtB gene, 21 were positive for cdt-I, three for cdt-II, four for cdt-III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 50 publications
2
47
0
Order By: Relevance
“…CDT [13] and SubAB [28] were identified as new types of toxin in STEC strains isolated from HUS patients. Although there are at least five types of CDT in E. coli [10], CDT-III and CDT-V have been detected in STEC strains [2,13]. It has been reported that cdt in eae-negative STEC was significantly more frequent in those from patients with HUS and in those from patients with diarrhea than in those from asymptomatic carriers [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CDT [13] and SubAB [28] were identified as new types of toxin in STEC strains isolated from HUS patients. Although there are at least five types of CDT in E. coli [10], CDT-III and CDT-V have been detected in STEC strains [2,13]. It has been reported that cdt in eae-negative STEC was significantly more frequent in those from patients with HUS and in those from patients with diarrhea than in those from asymptomatic carriers [2].…”
Section: Discussionmentioning
confidence: 99%
“…STEC O113:NM isolated in this study was used as a positive control for saa, lpfA O113 , cdt-V and subAB genes. These 4 PCR products were confirmed to be the corresponding genes by sequencing as described previously [10]. E. coli strain C600 was used as a negative control.…”
Section: Stec Strains Isolated From Healthy Cattlementioning
confidence: 99%
See 1 more Smart Citation
“…The sequences of all PCR products were matched with the 16S rRNA gene of the genus Providencia, but further differentiation at the species level was not possible, indicating that the PCR developed in this study was genus-specific. All positive samples were examined for other enteric pathogens such as enterohemorrhagic E. coli, enteroaggregative E. coli, Salmonella spp., Shigella spp., Campylobacter jejuni, C. coli, C. fetus, Norovirus, Adenovirus, and Rotavirus, by PCR or immune chromatography (10). P. rettgeri was the only pathogen that was isolated from the specimen from 1 child, while the other 3 children were shown to have had mixed infection with other pathogens (Table 2).…”
mentioning
confidence: 99%
“…in children with diarrhea in Japan. Recently we identified 2 isolates of P. alcalifaciens from children with diarrhea in Japan during a survey of cytolethal distending toxin-producing Escherichia coli in children with diarrhea (10,11). Therefore, we conducted a survey to determine the prevalence of Providencia spp.…”
mentioning
confidence: 99%